1991
DOI: 10.1620/tjem.165.99
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Ca2+, K+ and Glucose in the Medium for Sperm Penetration through the Human Zona Pellucida.

Abstract: When salt-stored human oocytes were inseminated in the regular mBWW medium and examined 6 hr later, the zonae of almost all of the oocytes were penetrated by spermatozoa. In contrast, none of zonae were penetrated when the oocytes were inseminated in either Ca2+-free, K+-free or glucose-free medium. The failure of zona penetration by spermatozoa in Ca2+-free and K+-free media is likely to be due to the inhibition of the acrosome reaction. Spermatozoa were unable to exhibit hyperactivated motility in glucose-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…Hyperactivation is the change in motility from low amplitude, progressive motility seen in freshly ejaculated or diluted epididymal sperm to a high-amplitude whiplash flagellar beat (Yanagimachi, 1994). It is thought to facilitate sperm transport in the oviduct and penetration of the zona pellucida (reviewed in Suarez, 1996) and glucose is required for hyperactivation and zona pellucida penetration by mouse (Fraser and Quinn, 1981;Cooper, 1984;Urner and Sakkas, 1996) and human sperm (Hoshi et al, 1991). Other energy substrates, including lactate, pyruvate, and glucose analogs that cannot be metabolized did not support hyperactivation in these studies, indicating a specific requirement for glycolysis.…”
Section: Glycolysismentioning
confidence: 85%
See 1 more Smart Citation
“…Hyperactivation is the change in motility from low amplitude, progressive motility seen in freshly ejaculated or diluted epididymal sperm to a high-amplitude whiplash flagellar beat (Yanagimachi, 1994). It is thought to facilitate sperm transport in the oviduct and penetration of the zona pellucida (reviewed in Suarez, 1996) and glucose is required for hyperactivation and zona pellucida penetration by mouse (Fraser and Quinn, 1981;Cooper, 1984;Urner and Sakkas, 1996) and human sperm (Hoshi et al, 1991). Other energy substrates, including lactate, pyruvate, and glucose analogs that cannot be metabolized did not support hyperactivation in these studies, indicating a specific requirement for glycolysis.…”
Section: Glycolysismentioning
confidence: 85%
“…This cytoskeletal structure is ideally positioned to serve as a scaffold for glycolytic enzymes, providing a mechanism for localized ATP production along the axoneme. Although ATP is also produced in the midpiece mitochondria, production of ATP via glycolysis is required for hyperactivated motility (Hoshi et al, 1991;Urner and Sakkas, 1996).…”
Section: Glycolytic Enzymesmentioning
confidence: 99%
“…Although oxidative phosphorylation is the main source and glycolysis is a minor source of ATP in most cell types, fertilization was not prevented by pharmacological inhibition of oxidative phosphorylation [22,24] or disruption of the testis-specific cytochrome C (Cyct) gene [25]. However, in vitro fertilization failed if the medium lacked glucose [24,[26][27][28][29], suggesting that glycolysis produces most of the ATP needed for sperm function. This was shown convincingly by using gene targeting to disrupt the sperm-specific Gapdhs gene.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that mammalian sperm produce lactate from glucose under aerobic conditions (Storey and Kayne 1975). Adenosine triphosphate production through glycolysis is required for hyperactivated sperm motility (Hoshi et al 1991;Urner and Sakkas 1996) and inhibition of oxidative phosphorylation does not block fertilisation (Fraser and Quinn 1981).…”
Section: Fuel Support and More: The Fibrous Sheathmentioning
confidence: 99%